Current Trends in the Use of Ultrasound Over Chest X-Ray to Identify Pneumothoraces in ICU, Trauma, and ARDS Patients. (January 2022) - Ron, Eyal; Alattar, Zana; Hoebee, Shelby; Kang, Paul; vanSonnenberg, Eric
Pneumothoraces are a common and potentially fatal complication for critically ill patients in the trauma and intensive care units. Since its use for pneumothorax detection was first reported in 1987, ultrasound has been increasingly used for the detection of thoracic injuries. As ultrasound imaging has improved and operators have potentially become more proficient, it is important to analyze more recent trends in the sensitivities and specificities of ultrasound for the detection of pneumothorax. This literature review and meta-analysis identifies 17 studies that directly compare the sensitivity and specificity of ultrasound and anterior-posterior chest x-ray in the identification of pneumothorax among 2955 patients who developed 793 pneumothoraces as detected by gold standard CT scanning. For the 17 articles analyzed, the pooled sensitivity of trans-thoracic ultrasound was 75.07% (64.92%-85.22%), and the pooled specificity was 98.36% (97.45%-99.26%). The pooled sensitivity of CXR was 45.65% (36.04%-55.26%), and pooled specificity was 99.62% (99.00%-100%). While this review demonstrates an improved sensitivity in the detection of pneumothorax with ultrasound over AP chest x-rays, it did not find a significant trend or improvement in the sensitivity or specificity of ultrasound for detecting pneumothorax over time.